Laboratory evaluation of geocell-reinforced gravel subbase over poor subgrades. Issue 2 (1st April 2013) - Lau, A.W.; Edil, T.B.; Tanyu, B.F.; Benson, C.H.; Aydilek, A.H.
Abstract : ABSTRACT: Large-scale experiments with cyclic loading were conducted to determine how incorporation of high-density polyethylene (HDPE) geocells affects the rutting properties of working platforms and resilient properties of a subbase in a pavement structure over soft subgrades. Four different geocells were used in this study to reinforce common subbase/base course gravel. Experiments were performed with 225 mm and 450 mm thick unreinforced and reinforced gravel and a crushed rock that is typically used for conventional cut-and-fill working platforms. Experiments were conducted to simulate loading conditions both during construction due to construction equipment and after construction due to traffic conditions over the asphalt pavement once the pavement structure is constructed. Materials used in this study were compacted to 90% relative compaction based on standard Proctor to determine the effect of geocells specifically with gravel material that is compacted to lower than typical standards. Deflections, modulus of subgrade reaction and resilient modulus of each section were evaluated. In summary, presence of geocells reduced the plastic deflection of the working platforms by 30–50%, improved the resilient modulus of the subbase by 40–50%, and the modulus of subgrade reaction by more than 2 times.